Perception and problem of infrastructure usage in Kedah - Yusoff, Noraniza; Talib, Azlizan; Pon, Yusuf (2017)
Infrastructure for instance roads, mines and hydroelectric dams, are spreading rapidly. Infrastructure arrangements are the essential of the countries’ economy and welfare; infrastructure creates vital services that concern on people’s living, and each sector that regards to the community. The problem of low infrastructure usage reduced the probability of poor perception towards infrastructure. Why are some social groups reporting low perceptions compared to other social groups? This study aims to provide an explanation of the relationship between perception toward infrastructure and problem of infrastructure usage. Quantitative approach has been used for data collection and analysis on 321 samples. Through correlation analysis, result shows a very weak negative association between perception toward infrastructure and problem of infrastructure usage. Increase in perception toward infrastructure expected decrease problem of infrastructure usage.